Brown adipose tissue thermogenesis among a small sample of reindeer herders from sub-Arctic Finland - Ocobock, Cara; Soppela, Päivi; Turunen, Minna; Stenbäck, Ville; Herzig, Karl-Heinz (Journal of Physiological Anthropology, 2022)
Introduction Interest in human physiological responses to cold stress have seen a resurgence in recent years with a focus on brown adipose tissue (BAT), a mitochondria dense fat specialized for heat production. However, a majority of the work examining BAT has been conducted among temperate climate populations. Methods To expand our understanding of BAT thermogenesis in a cold climate population, we measured, using indirect calorimetry and thermal imaging, metabolic rate and body surface temperatures of BAT-positive and BAT-negative regions at room temperature, and mild cold exposure of resting participants from a small sample of reindeer herders (N = 22, 6 females) from sub-Arctic Finland. Results We found that most herders experienced a significant mean 8.7% increase in metabolic rates, preferentially metabolized fatty acids, and maintained relatively warmer body surface temperatures at the supraclavicular region (known BAT location) compared to the sternum, which has no associated BAT. These results indicate that the herders in this sample exhibit active BAT thermogenesis in response to mild cold exposure. Conclusions This study adds to the rapidly growing body of work looking at the physiological and thermoregulatory significance of BAT and the important role it may play among cold stressed populations.